Accessibility and diversity: Deaf space in action - Per Koren Solvang; Hilde Haualand (Scandinavian Journal of Disability Research, 2013)
How disabled people gather and share common experiences is empirically not a well-addressed issue in discussions about disability identity and unity. Among Deaf people, there is a long tradition for meeting in transnational contexts. Based on an intensive multi sited fieldwork at several transnational events, the article presents some examples of how deaf people negotiate social positions as Deaf that value difference. They gather as a community of communicators, marked by an identification founded on sharing one another's languages, common histories and through strong similarities in terms of culture and feeling oppressed by the hearing society. The identity negotiations taking place at these meeting places prove relevant to disabled people in the way they explore pressing issues such as accessibility and conflicting perspectives on what a disability shall mean in the lives of people affected by impairment.